High performance graphene oxide/NiAl2O4 directly grown on carbon cloth hybrid for oxygen evolution reaction. (22nd September 2022) - Aman, Salma; Farid, Hafiz Muhammad Tahir; Manzoor, Sumaira; Ashiq, Muhammad Naeem; Khosa, Rabia Yasmin; Elsayed, Khaled A.; Mahmoud, K.H.; Taha, T.A.; Waheed, Muhammad Suleman; Abdullah, Muhammad
Abstract: Due to the lethargic kinetics, the oxygen evolution reaction (OER) requires a high anodic voltage, restricting the efficiency as well as practical applications for electrochemical water splitting. For this purpose, metal oxides (M − O) are viewed as a potential competitor in this search because of their high redox potential. Still, their low conductivity and instability are two significant barriers that must be addressed. In this study the nanocomposite of NiAl2 O4 with graphene oxide (GO) as a highly effective and long-lasting electrocatalyst for OER has been fabricated. In an alkaline (1.0 M KOH) medium, the GO/NiAl2 O4 responds to a very sharp overpotential of 219 mV at a current density of 10 mA/cm 2 and with a lower value of tafel slope (43 mV/dec) as compared to its counterparts. The GO/NiAl2 O4 corresponds to the high stability of 18 h with retained crystal structure and morphology. For the expected prolonged OER process, we assume the active redox couple due to the presence of Ni +2/+3 metal in NiAl2 O4 varies periodically. Furthermore, the synergistic effect of NiAl2 O4, combined with the GO, facilitates the dynamics of O2 evolution as a final product, and are useful for further applications in future era. Highlights: A simple in-situ growing strategy was used to design a novel NiAl2 O4 nanomaterial with GO as an OER catalyst. XRD, SEM and EDS have all been used to characterize GO, NiAl2 O4 and GO/NiAl2 O4 materials. All of the findings show that carbon-based composites can improve the sample's conductivity. The current concept proposes and investigates a new efficient strategy to replace precious metal electrocatalysts.